Liver Fibrosis in HCV Monoinfected and HIV/HCV Coinfected Patients: Dysregulation of Matrix Metalloproteinases (MMPs) and Their Tissue Inhibitors TIMPs and Effect of HCV Protease Inhibitors - Latronico, Tiziana (Int J Mol Sci, 2016)
An imbalance between matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) may contribute to liver fibrosis in patients with hepatitis C (HCV) infection. We measured the circulating levels of different MMPs and TIMPs in HCV monoinfected and HIV/HCV coinfected patients and evaluated the potential for anti-HCV therapy to modulate MMP and TIMP levels in HCV subjects. We analyzed 83 plasma samples from 16 HCV monoinfected patients undergoing dual or triple anti-HCV therapy, 15 HIV/HCV coinfected patients with undetectable HIV load, and 10 healthy donors (HD). Levels of MMP-1, MMP-2, MMP-3, MMP-8, MMP-9, MMP-10, TIMP-1, and TIMP-2 were measured by a SearchLight Multiplex Immunoassay Kit. MMP-2 and MMP-9 were the highest expressed MMPs among all the analyzed samples and their levels significantly increased in HCV monoinfected and HIV/HCV coinfected subjects compared to HD. TIMP-1 levels were significantly higher in HCV and HIV/HCV subjects compared to HD and were correlated with liver stiffness. These findings raise the possibility of using circulating TIMP-1 as a non-invasive marker of liver fibrosis in HCV infection. A longitudinal study demonstrated that MMP-9 levels significantly decreased (40% reduction from baseline) in patients receiving dual as well as triple direct-acting antivirals (DAA) anti-HCV therapy, which had no effect on MMP-2, TIMP-1, and TIMP-2. As the dysregulation of MMP-2 and MMP-9 may reflect inflammatory processes in the liver, the decrease of MMP-9 following HCV protease inhibitor treatment suggests a positive effect on the reduction of liver inflammation.